Critical success aspects in project management: similarities and differences between the construction and the software industry - Varajão, João (2014)
Project success is highly dependent on the project management process, and there are several aspects that need to be carefully considered. This article aims at responding to the research question: are there similarities in different industries in what concerns the critical aspects for the success of project management? Throughout a comprehensive survey applied to medium and large companies of the construction and software industries, we came to the conclusion that the two currently most important project management success aspects are common to both industries: "project planning" and "well defined objectives and requirements". The "project manager efficiency" is also in the top of the critical success aspects. On the other hand, other aspects show major differences in the studied industries.